Non-Penal Policy of Syariah Institutions in Preventing Juveniles from Narcotics Abuse in Aceh Province, Indonesia - Zaituni Zaituni; Riza Nizarli; M Yakub Aiyub Kadir (Jambe Law Journal, 2021)
This paper aims to discuss non-penal policies of Syariah institutions through families and educational institutions in preventing juvenile from committing narcotics abuse under the Aceh Qanun on Drug Abuse Prevention Facilities. Originally, a normative legal research, res covering legislative review and supporting with data that found in the field and stakeholders interview as supporting data in the use of research methodologies. The result indicates that Aceh syariah institutions are authorized to carry out non-penal policies in preventing child or juvenile narcotics abuse, as known under sadd adz-dzari’ah in islamic methodology (usul fiqh). However, to date, the application of preventive measures through family and educational institutions has not had any progress yet. Hence this paper suggests Syariah institution in Aceh, including Dinas Syariah Islam, Aceh Ulama Assembly, Dayah Body and Aceh Syariah Police in collaboration with Anti Narcotic Institution, to pay serious attention to non-penal policies to ensure the children safe from narcotics acts. This contributes to highlight the prevalence of non-penal policy can be more effective rather than penal policy in preventing children from narcotics abuses in Aceh province, Indonesia